Post-synthesis of covalent organic frameworks with dual-hydrophilic groups for specific capture of serum exosomes - Hua, Shuwen; Feng, Quanshou; Xie, Zehu; Mao, Haijiao; Zhou, Yuping; Yan, Yinghua; Ding, Chuan-Fan (Journal of Chromatography A, 2022)
•A hydrophilic COF was prepared via the post-synthesis modification strategy.•COF-S@Au@GC was used for selective enrichment glycosylated exosomes in serum.•182 glycopeptides were detected from serum after treated with COF-S@Au@GC. Exosomes can reflect the physiological state of parent cells and are potential disease biomarkers. In this study, we developed an innovative hydrophilic material by post-synthesis of covalent organic frameworks with dual hydrophilic groups of glutathione and cysteine (denoted as COF-S@Au@GC) to detect glycosylated exosomes in human serum. COF-S@Au@GC enriched glycosylated exosomes in human serum due to glutathione and cysteine (GC) hydrophilicity. Our results show that COF-S@Au@GC has a detection limit of 5 amol μL−1, selectivity of 1:2000, size-exclusion effect of 1:10,000, repeatability of 10 cycles, recovery of 98.3 ± 0.5%, and loading capacity of 50 mg g−1 for glycopeptides. In addition, 182 glycopeptides were detected after enrichment with COF-S@Au@GC from renal carcinoma serum, demonstrating the feasibility of enriching glycopeptides from complex biological samples. Furthermore, COF-S@Au@GC successfully captured glycosylated exosomes in the serum of renal cancer patients, with their 161 glycopeptides detected by nano liquid chromatography with tandem mass spectrometry (LC-MS/MS). This study provides a new heuristic strategy for isolating exosomes and contributes to further functional analysis of exosomes.